Calculus with Applications (10th Edition)

Published by Pearson
ISBN 10: 0321749006
ISBN 13: 978-0-32174-900-0

Chapter 12 - Sequences and Series - 12.1 Geometric Sequences - 12.1 Exercises - Page 613: 36



Work Step by Step

We are given $\Sigma\frac{3}{2}(-2)^{i}$ with $a=\frac{3}{2}, r=-2$ the summation is from $i=0$ to $n-1=5 \rightarrow n=6$ using the formula $S_{n}=\frac{a(r^{n}-1)}{r-1}$ $r \ne 1 $ gives $S_5=\frac{3}{2}(\frac{(-2)^{6}-1}{-2-1})$ $=\frac{-63}{2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.